AI Analysis in Digital Cultural Transformation: Theories, Cases, and Their Implications for Society - Abd. Gaffar (International Journal Labs, 2025)
This article explores the transformation of digital culture through the in fluence of artificial intelligence (AI), focusing on how these technologies are changing the way individuals and communities interact with media, technology, and social policy. AI, increasingly integrated in various aspects of everyday life, affects forms of social interaction, information distribution, as well as identity and cultural formation. Through the analysis of various current concepts, theories, and case studies. This article identifies AI's key role in creating more per sonal and directed digital experiences, while exploring emerging ethical and social challenges. The research combines theories of social construction of technology, posthumanism, and social criticism of technology to provide a deeper understanding of AI's impact on contemporary society and culture. Key findings suggest that while AI offers great potential in improving accessibility and efficiency, the use of these technologies can also worsen social inequality and increase control of surveillance. This article suggests the need for more rigorous regulations to regulate AI use and optimize its positive impact, as well as the need to continue to develop an understanding of the interaction between humans and machines in social and cultural contexts. This research contributes to critical thinking about AI's role in shaping digital culture and provides direction for furthers research as well as more inclusive and ethical policies in the development of these technologies..